Severe Congestive Dysmenorrhea in an Adolescent - Swaramya Chandrasekaran; Haritha Sagili; Sunitha V Chakkalakkoombil (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2017)
A 16 year old girl presented with severe congestive dysmenorrhea shortly after the onset of menarche at 14 years of age. Menstrual cycles were otherwise regular with normal fl ow pattern. She was prescribed multiple NSAIDS, which provided minimal relief.